Healthy lifestyle and life expectancy at age 30 in the Chinese population: an observational study - Sun, Qiufen (Lancet Public Health, 2022)
BACKGROUND: The improvement of life expectancy is one of the aims of the “Healthy China 2030” blueprint. We aimed to investigate the extent to which healthy lifestyles are associated with life expectancy in Chinese adults. METHODS: We used the prospective study of China Kadoorie Biobank (CKB) study (n=487,209) to examine the relative risk of mortality associated with individual and combined lifestyle factors (never smoking or quitting not for illness, no excessive alcohol use, being physically active, healthy eating habits, and healthy body shape). We estimated the national prevalence of lifestyle factors using data from the China Nutrition and Health Surveillance (2015) and derived mortality rates from the Global Burden of Diseases, Injuries, and Risk Factors Study (2015). All three data sources were combined to estimate the life expectancy of individuals at age 30 following different levels of lifestyle factors by using life table method. The cause-specific decomposition of the life expectancy differences was analyzed using Arriaga’s method. FINDINGS: There were 42,496 deaths documented over a median follow-up of 11.1 (interquartile range: 10.2-12.1) years in CKB. The adjusted hazard ratios (95% confidence intervals [CIs]) of participants adopting five versus 0-1 low-risk factors was 0.38 (0.34, 0.43) for all-cause mortality, 0.37 (0.30, 0.46) for cardiovascular disease (CVD) mortality, 0.47 (0.39, 0.56) for cancer mortality, and 0.30 (0.14, 0.64) for chronic respiratory disease (CRD) mortality. The life expectancy (95%CI) at age 30 for individuals with 0-1 low-risk factor was on average 41.7 (41.5, 42.0) years for men and 47.3 (46.6, 48.0) years for women. When individuals adopted all five low-risk factors, the life expectancy was 50.5 (48.5, 52.4) years for men and 55.4 (53.5, 57.4) years for women, with an increase (95%CI) of 8.8 (6.8, 10.7) years (men) and 8.1 (6.5, 9.9) years (women), respectively. The estimated extended life expectancy for men and women was attributable to reduced death from CVD (2.4 years [27% out of the total extended life expectancy] for men and 3.6 years [46%] for women), cancer (2.5 years [29%] and 0.9 years [11%]), and CRD (0.6 years [7%] and 1.3 years [16%]). INTERPRETATION: Our findings suggest that increasing the adoption of these five healthy lifestyle factors through public health interventions could be associated with substantial gains in life expectancy in the Chinese population.